A new species and key to all known species of the genus Filchnerella Karny, 1908 from China (Orthoptera: Acridoidea, Pamphagidae) - Cao, Cheng-Quan; Li, Xin-Jiang; Yin, Zhan (Zootaxa, 2018)
The new species i.e. Filchnerella wuhaiensis sp. nov is described from Inner Mongolia Autonomous Region, China. The new species is similar to Filchnerella helanshanensis Zheng, 1992, but differs from the latter by 21-segmented antennae, prozona of pronotum higher than metazona, length of tegmina 2.0 times maximum width, width of interspace of mesosternum 1.2 times length and lower margin of hind femur not red in male. A key to all species of the genus Filchnerella Karny, 1908 is given in this paper. Two genera Pseudotmethis Bey-Bienko, 1948 and Paratmethis Zheng & He, 1996 are valid genus and not a synonym of Filchnerella Karny, 1908. Type specimens are deposited in the College of Life Sciences, Hebei University, Baoding, Hebei, China.